THE ANALYSIS OF RECIPROCAL TEACHING LEARNING MODEL IN IMPROVING CRITICAL READING SKILLS AT JUNIOR HIGH SCHOOL - Rita Safira; Masrupi; Welliam Hamer (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Reciprocal Teaching Model in improving students’ critical reading skills at SMPN 7 Kota Serang. This research employed a qualitative descriptive method. Data were collected through classroom observation, critical reading tests, and semi-structured interviews with both the English teacher and Grade VIII students. The data were then analyzed using descriptive analysis to examine patterns of teacher implementation, student engagement, and reading achievement. The findings reveal that the Reciprocal Teaching Model was implemented at a Good level (mean score 3.4 for teacher performance) and produced an average critical reading achievement of 58.75%. Students performed best in identifying main ideas (70%) but struggled with evaluating texts critically (55%) and expressing opinions (50%). This study concludes that the Reciprocal Teaching Model is an effective strategy for developing students’ critical reading skills, though sustained scaffolding for higher-order tasks remains essential for optimal outcomes